Advantages and disadvantages of multifocal contact lens correction of presbyopia in patients with myopic refraction - A. G. Shchuko (Oftalʹmologiâ, 2014)
Purpose: To evaluate the results of multifocal contact correction of presbyopia in subjects with myopic refraction. Methods: The study included 28 patients with myopia (range 43 to 54 years) in conditions of routine contact correction of vision. The examination was repeated a month later after wearing of multifocal contact lenses. The following parameters were assessed: far visual acuity, near and intermediate visual acuity (monocular and binocular), spatial contrast sensitivity, stereo vision (Lang test I&II), area of binocular interaction (binarymeter), visual quality (test VF-14). Results: The indices if visual acuity in patients with multifocal contact lenses were high at all test distances. The significant increase of near vision was noted: visual acuity with monofocal contact correction was 0.39±0.11, with multifocal — 0.62±0.15 (p<0.05). However the decrease of spatial contrast sensitivity was noted: with monofocal contact lenses 21.96±4.6 dB (total in 4 frequencies), with multifocal — 19.48±1.1 dB, p<0.05. The level of stereo perception in users of multifocal contact lenses remains high, but the decrease of fusion capacity in convergence was noted. The greatest satisfaction with obtained vision was noted by patients, who achieved refraction (-) 0.5 D or difference between eyes 0.3‑0.5 D. The office employees were maximally satisfied with multifocal contact lenses. Conclusion: Multifocal contact correction of presbyopia allows achieving high functional results at different distances. Patients with myopia, previously used contact lens correction, easy pass to multifocal correction options. The greatest satisfaction with obtained vision was noted by patients, who achieved refraction (-) 0.5 D.